Paradigma Baru dalam Pembaharuan Kitab Undang-Undang Hukum Perdata: Upaya Adaptasi terhadap Dinamika Hukum di Era Digital dan Globalisasi - Ni Komang Irma Adi Sukmaningsih; I PUTU ANDIKA PRATAMA; Anak Agung Gede Agung Indra Prathama (Fakultas Hukum Universitas Ngurah Rai, 2025)
The Indonesian Civil Code (KUHPerdata), a legacy of colonial law, has been in effect for over a century and is increasingly unable to address the normative challenges posed by the digital era and globalization. These include the lack of regulation concerning electronic transactions, personal data protection, digital assets, and cross-border dispute resolution. This study aims to assess the current capability of KUHPerdata to meet modern legal demands and to propose a renewal approach based on relevant legal principles and theories of legal formation. Using a normative juridical method with a statute approach, this research analyzes primary, secondary, and tertiary legal materials through descriptive analysis. The findings reveal significant normative limitations of KUHPerdata in responding to socio-economic and technological transformations. Legal reform is therefore urgently required, based on the principles of justice, legal certainty, freedom of contract, and consumer protection, and grounded in legal theories such as natural law, legal positivism, progressive law, and living law. The renewal must aim to create a responsive and globally integrative civil law system that can accommodate technological advancements and international legal standards. In conclusion, reforming KUHPerdata is not only a legal necessity but also a strategic effort to enhance Indonesia’s legal competitiveness in the global legal landscape.